2023
DOI: 10.14507/epaa.31.7364
|View full text |Cite
|
Sign up to set email alerts
|

Charter schools after three decades: Reviewing the research on school organizational and instructional conditions

Abstract: Charter school policies have focused on improving three aspects of schools—autonomy, innovation, and accountability—with the intention of promoting advances in curriculum, instruction, and learning that lead to better student outcomes. However, most research on charter schools tends to neglect school organizational and instructional conditions. Overall, reviews show that charter schools have inconsistent effects on student achievement scores, a finding that masks heterogeneous effects among different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 91 publications
0
2
0
3
Order By: Relevance
“…As CS estão amplamente estudadas (e continuam a sê-lo) nos diversos contextos em que estão estabelecidas. As controvérsias, os debates, as vantagens e desvantagens que se lhes sobrepõem estão devidamente documentados (Dallavis;Berends, 2023;Mullen;Bartlett, 2022;Ravitch, 2014). Todas as questões, sugestões, recomendações e reflexões, sobretudo éticas e políticas, resultantes dessas investigações devem servir de base para problematizar a suposta vantagem competitiva e econômica da sua implementação em sistemas educativos onde não existem.…”
Section: Considerações Finaisunclassified
See 2 more Smart Citations
“…As CS estão amplamente estudadas (e continuam a sê-lo) nos diversos contextos em que estão estabelecidas. As controvérsias, os debates, as vantagens e desvantagens que se lhes sobrepõem estão devidamente documentados (Dallavis;Berends, 2023;Mullen;Bartlett, 2022;Ravitch, 2014). Todas as questões, sugestões, recomendações e reflexões, sobretudo éticas e políticas, resultantes dessas investigações devem servir de base para problematizar a suposta vantagem competitiva e econômica da sua implementação em sistemas educativos onde não existem.…”
Section: Considerações Finaisunclassified
“…Resumidamente, as CS são escolas públicas geridas por entidades privadas que podem ser constituídas por professores, famílias, empresas ou outros atores da sociedade civil, em consórcio ou individualmente (Dallavis;Berends, 2023;Mullen;Bartlett, 2022). Estas escolas, criadas por contratualização entre a entidade gestora e o estado, são de frequência gratuita, financiadas sobretudo pelo Estado, mas que, dependendo da regulamentação estatal, podem recorrer a outras fontes de financiamento (fundações, empresas, patrocinadores individuais) e obter fins lucrativos.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Organizational contexts of schooling, including how classes are structured, have been linked to student outcomes for decades (e.g., Barr & Dreeben, 1983;Dallavis & Berends, 2023;Gamoran, Nystrand, et al, 1995;Gamoran, Secada, et al, 2000). Within-school differences, including distinct curricular pathways and access to resources, have consequences for student learning and performance (Domina et al, 2023).…”
Section: The Organization Of De Programmingmentioning
confidence: 99%
“…However, studies that evaluate charter schools based on student-level performance are more varied, with reported positive [88,89,91,92], negative [87,93,94], and null effects [95][96][97]. It is worth pointing out that studies that have found positive effects tend to be lottery-based studies [98], which require charter schools to be over-enrolled to be included, meaning family and student interest in these schools exceed their enrollment capacity. Over-enrollment in charter schools can be indicative of their academic success, and thus the findings might not be generalizable across all charter schools.…”
Section: Student Academic Outcomesmentioning
confidence: 99%